Taxation and Dividend Policy: The Muting Effect of Agency Issues and Shareholder Conflicts. (31st May 2017) - Jacob, Martin; Michaely, Roni
Abstract : Using proprietary data on the entire spectrum of ownership structure and exact tax status of investors and firms, we examine how dividend taxation affects payout. Utilizing an exogenous shock to dividend taxation, we show that absent any frictions, dividend taxation has a large impact on payout. As agency issues and shareholder conflicts increase, owners' tax preferences have significantly smaller impact on payout. Three mechanisms reduce the dividend-tax sensitivity: Coordination among owners, heterogeneity in tax preferences, and diverging objectives between managers and owners. Altogether, taxation has a first-order impact on payout, but agency issues and shareholder conflicts mute its impact substantially. Received June 20, 2016; editorial decision January 24, 2017 by Editor Francesca Cornelli.